From Business Modelling to the Leadership and Innovation in Business: Bibliometric Analysis (Banking as a Case) - Tetiana Goncharenko (Business Ethics and Leadership)
The analysis of approaches to defining the banking business model showed that digital financial technologies, e-commerce, information management are important factors that form the model of leadership and innovation in business. The development of risk management, risk assessment, profitability-risk-stability triangle balancing, which create relevant trends in the formation of business leadership models, has increasing importance for managers, clients and shareholders. The article identifies the dominant tendencies in the development of scientific thought (based on 6377 articles from 1991-2019 in journals indexed by Scopus and Web of Science) regarding the transformation of business models in banks and the future research directions with the help of bibliometric analysis (VOSviewer). The conducted analysis showed that in 2012-2017 the number of scientific articles about the transformation of banks’ business models began to increase. It proves the relevance of business modelling for leadership and innovation in business. At the same time, the focus of research has shifted from general strategic management issues to risk management issues. In 2017, the number of articles studying the banking business model increased by 148% compared to 2012. Therefore, these articles in the subject area observe such areas as business, management, economics, econometrics, finance, social and computer sciences. Among the scientists who studied the banks’ business models, most are scientists from the US, UK and India. In 2018, there was a significant increase in the number of articles on banking strategic management published in high impact journals, such as the Journal of Banking and Finance, the International Journal of Bank Marketing and Economic Modeling. The use of the VOSviewer has identified 8 research clusters exploring the issue from different perspectives. The first (largest) cluster consists of studies that examine banks’ business models through decision-making and information management technologies, risk assessment and minimization mechanisms, the relationship between banking sales dynamics and the information databases etc. The second-largest cluster brought together researchers examining banks’ business models in terms of the financial crisis effects, regulatory changes, business efficiency and stability (z-score), etc. The third-largest cluster is the study of business models through the dynamics of transformations in the financial market, in lending behaviour and business cycles. These three largest clusters confirm that the key to leadership and innovation in banking is the balance between the profitability-risk-stability triangle and information technology.